1994
DOI: 10.1254/jjp.64.115
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Profiles of a Novel Aldose Reductase Inhibitor, SPR-210, and Its Effects on Streptozotocin-Induced Diabetic Rats

Abstract: ABSTRACT-SPR-210{2-[4-(4,5,7-trifluorobenzothiazol-2-yl)methyl-3-oxo-3,4-dihydro-2H-1,4-benzo thiazin-2-yl] acetic acid}, a novel aldose reductase (AR) inhibitor, exhibited highly potent inhibition of partially purified AR from porcine lens (IC50=9.5 x 10-9 M) and human placenta (IC50=1.0 x 10-'M). On the other hand, very weak inhibition by SPR-210 was observed against human placenta aldehyde reductase, which is the most closely related enzyme to AR, and against several adeninenucleotide-requiring enzymes. SPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 34 publications
0
20
1
Order By: Relevance
“…Treatment with GP-1447 dose-dependently amelio rated the slowed MCV with an ED50 value of 0.28 mg/kg/day, indicating that this compound is approxi mately twenty times more potent than SG-210 in restoring the reduced MCV. In contrast to our results, SG-210 has been reported to recover the reduced MCV, the ED50 value being 0.5 mg/kg/day (17). The reason for this dis crepancy is unclear, but may be due to the different methods used.…”
Section: Discussioncontrasting
confidence: 99%
“…Treatment with GP-1447 dose-dependently amelio rated the slowed MCV with an ED50 value of 0.28 mg/kg/day, indicating that this compound is approxi mately twenty times more potent than SG-210 in restoring the reduced MCV. In contrast to our results, SG-210 has been reported to recover the reduced MCV, the ED50 value being 0.5 mg/kg/day (17). The reason for this dis crepancy is unclear, but may be due to the different methods used.…”
Section: Discussioncontrasting
confidence: 99%
“…Although several reports in the literature indicate that ARIs inhibit sugar cataracts through the inhibition of enzyme AR (Unakar and Tsui, 1983;Harries et al, 1985;Unakar et al, 1985), many ARIs have side effects when administrated systemically. Moreover, it was previously reported that the effect of AR inhibitors such as epalrestat (Terashima et al, 1984), tolrestat (Simard-Duquesne et al, 1985), zenarestat (Ao et al, 1991), SG-210 (Matsui et al, 1994) and SNK-860 (Mizuno et al, 1992) on cataract formation is inadequate in spite of their potent ameliorating effect on the decreased motor nerve conduction velocity in diabetic animals. Thus, a synthetic compound such as epalrestat is not proper as an anti-cataract drug in diabetic animal model.…”
Section: Discussionmentioning
confidence: 99%
“…However, in hyperglycemia, markedly increased production of sorbitol ensues. This process has long been hypothesized to be linked to the development of diabetic retinopathy, neuropathy and nephropathy (19,22,47). In certain populations, recognized polymorphisms in the aldose reductase gene have been associated with increased complications (29,39).…”
Section: Direct Consequences Of Hyperglycemiamentioning
confidence: 99%